Rejecting the criminal narrative: Designing a plagiarism avoidance tutorial. Issue 4 (2nd October 2019) - Diamond, Kelly
Abstract: Librarians are often asked to create instructional experiences and/or learning objects to teach students to avoid plagiarizing. Creating an effective tutorial not only requires following good instruction design principles but also understanding why and when students plagiarize and how to address students effectively about plagiarism. This article explains how one university library created a tutorial informed by current research regarding plagiarism and negative discourse surrounding plagiarism and plagiarists. This tutorial avoided criminal and accusatory narratives; addressed why students might plagiarize either intentionally or unintentionally; and was built within a course management system so that it could be used in multiple courses.